Arthrocentesis in Temporomandibular Joint disc Derangement Patients, with and without Hyaluronic Acid, A Clinical Trial - Zuhair Mehdi, Maimoona Siddiq, Usman Ul Haq, Fatima Khattak, Adam Khan Danish, Hamza Hassan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Our research looked at the effectiveness of arthrocentesis in the treatment of TMJ issues with and without the addition of hyaluronic acid. Study Design: Prospective study Place and Duration: Dental College, HITEC-IMS, Taxila Cantonment. December 2019- May 2022 Methods: In this study 60 patients of both genders who had temporomandibular Joint disc derangement disorders were presented. After obtaining informed written consent, the demographics of enrolled patients were analyzed, including age, sex, side, and type of effusion. In two groups, patients were split evenly. Group I received arthrocentesis alone with lavage and group II received arthrocentesis with hyaluronic acid. We used standard two needle arthrocentesis among all cases. Post treatment effectiveness among both groups were assessed and compared in terms of maximum mouth opening, reduction in pain score and complications. SPSS 24.0 version was used to analyzed completed data. Results: There were majority females in group I was 20 (66.7%) and in group II was 23 (76.7%). Mean age of the patients in group I was 34.6±11.44 years and had mean BMI 22.8±7.28 kg/m2 while in group II mean age was 32.11±14.34 years with mean BMI 21.5±8.41 kg/m2. Right side was the most common side among both groups found in 16 (53.3%) in group I and 17 (56.7%) in group II. In group I effusion in upper compartment found in 22 (73.3%) cases while in group II 24 (80%) cases had upper compartment. Pre-operative maximum mouth opening in group I was 30.4±9.45 mm and in group II MMO was 31.9±14.41. Post-operative we found increased in MMO in group I was 42.6±12.32 mm and in group II 44.7±11.29 mm but no any significantly difference was observed after 2 years of follow up 39.3±15.49 in group I and 41.13±6.51 mm in group II. Post-operative reduction in pain score was observed 1.8±5.1 in group I and 0.1±1.9 in group II by using VAS significantly with p value <0.003. Conclusion: We concluded in this study that the arthrocentesis is an effective and safe method in the treatment of temporomandibular joint disc derangement in terms of increase in MMO and reduction in pain score while arthrocentesis with hyaluronic acid showed better results but difference was not significant.